PENGARUH APLIKASI PULSA GATING TERHADAP CITRA ARTERI KAROTIS PADA PEMERIKSAAN MAGNETIK RESONANS ANGIOGRAFI DENGAN MENGGUNAKAN PERALATAN MRI 0,3 TESLA DI RUMAH SAKIT TELOGOREJO SEMARANG - Utama, Nur; Puji Utami, Asih; Rosidah, Siti (Jurnal Ilmu dan Teknologi Kesehatan, 2010)
????????? Magmetic resonance angiography (MR Angiography) is a sequence of MRI examination to study blood vascular system with or without introduce of contrast agent. Carotid arteries, part of blood vascular system commonly studied by doing MRA exam. Time of Flight (TOF), one of the methods of MRA exam that can be perform blood vessels or flowing spin as a bright image, without introduce contrast agent into blood vessels. Pulse gating application on carotid arteries MR Angiography exam? reduces cardiac pulsation effect, So the image looks better. The purpose of the research to findout the influence of pulse gating aplicationon on carotid arteries image of MRA exam use 0.3 Tesla MRI apparatus at Telogorejo hospital in Semarang.????????? Type of the research is pre-experiment with descriptive methode. Data collected by doing MRA exam of extra cranial carotid arteries on a volunteer in Telogorejo hospital, with and without pulse gating application. Conspicuity of images appears by measuring Signal to Noise Ratio and Contrast to Noise Ratio on image of flowing spin of carotid arteries and supported by opinion of five Radiologists in Semarang. Data analysis use statistic procedure and descriptive methode. Measuring SNR use software of computer of MRI unit and CNR value obtained by reducing SNR value of flowing spin with SNR value of stationary spin.? ????????The result of the research shown that application of pulse gating influence the quality of image on MRA carotid arteries.?Key word :? Carotid arteries, pulse gating, image quality, 0.3 Tesla.